Monday

April 21, 2014

April 21, 2014

Posted by **Juan** on Sunday, August 14, 2011 at 8:25pm.

sq root of (x+6) = x

- Algebra2 -
**Damon**, Sunday, August 14, 2011 at 8:36pm(x+6)^.5 = x

multiply both sides by (x+6)^.5

(x+6) = x(x+6)^.5 but (x+6)^.5 is x

so

x+6 = x^2

x^2 - x - 6 = 0

(x-3)(x+2) - 0

so x = 3 or x=-2

try x = 3

sqrt(9) = 3 sure enough

try x = -2

sqrt (4) = -2 nope, negative root does not check

so x = 3 is the answer.

**Related Questions**

Algebra - Can you explain how to find the solution of 3x^2-2x+5, using the ...

Algebra - I had to solve 2x^2-x-1 using the quad. formula. I got it down to (1...

Algebra - I had to solve the function g of f where f is x^2+1 and g is sq. root ...

Trigonometry - I'm trying to find the cosecant of 11 pi/6. The answer is -2, but...

Math - 1) Solve equation 3r+5 _____ + 2 = 2r to find the value of r? 2 A. 2 1/7 ...

Calculus I - Find the derivative ** (sq root) y = (square root) x + (2nd sq root...

Trig. - Can you please review this to see if I did this right? 2cos^2x+3cosx=0 ...

Roots and Pre-cal - Find the roots of the function f(x)= x^2 +2x+2 a)-1 + sq ...

math - simplify square 48/square6 square root(48) is the same as sq root (8) x ...

college algebra - Solve: sq root of (x+1) minus 3 = sq root of (x+4) when I ...